Analisis Pentingnya Pengelolaan Kurikulum di Sekolah Dasar - Prastiwi, Maulia Widya; Nur Azizah, Lintang; Kurniawan, Zahri; Apriliana, Gita; Susanto, Bahtiyar Heru (Indo-MathEdu Intellectuals Journal, 2024)
Improving curriculum management standards must continually be pursued to achieve optimal curriculum management goals, particularly at the elementary school level. This study aims to explore the importance of curriculum management in elementary schools. The method used is qualitative with a literature review approach involving analysis of literature from various sources such as books, articles, and other documents. Miles and Huberman's analysis is employed to analyze qualitative data, including data reduction, data display, and conclusion drawing. The research findings indicate that curriculum management plays a crucial role in supporting educational sustainability. However, in practice, curriculum management faces various challenges, both from educators and students. Ongoing efforts are being made to ensure smooth curriculum implementation and minimize potential obstacles throughout the process